Making a meaningful contribution to theory. Issue 9 (7th September 2015) - Brian Fynes and Professor Paul Coughlan, Professor; Boer, Harry; Holweg, Matthias; Kilduff, Martin; Pagell, Mark; Schmenner, Roger; Voss, Chris
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The need to make a "theoretical contribution" is a presumed mandate that permeates any researcher's career in the Social Sciences, yet all too often this remains a source of confusion and frustration. The purpose of this paper is to reflect on, and further develops, the principal themes discussed in the "OM Theory" workshop in Dublin in 2011 and the special sessions at the 2011 and the 2013 EurOMA Conferences in Cambridge and Dublin. Design/methodology/approach – This paper presents six short essays that explore the role and use of theory in management research, and specifically ask what is a good or meaningful contribution to theory. The authors comment on the current state of theory in Operations Management (OM) (Harry Boer), the type of theories the authors have in OM (Chris Voss), the role of theory in increasing the general understanding of OM problems (Roger Schmenner), whether the authors can borrow theories from other fields or actually have theory "of our own" (Matthias Holweg), the different ways in which a contribution to theory can be made (Martin Kilduff), and how to construct a theoretical argument (Mark Pagell). Findings – The authors argue that theory is fundamental to OM research, but that it is not the inevitable starting point; discovery and observation are equally important and often neglected avenues to contributing to theory. Also, there is no one right way to making a contribution, yet consistency between ontology, epistemology, and claimed contribution is what matters. The authors further argue that the choice of theory is critical, as a common mistake is trying to contribute to high-level theories borrowed from other fields. Finally, the authors recommend using theory parsimoniously, yet with confidence. Originality/value – The paper presents a collection of viewpoints of senior scholars on the need for, and use of, theory in OM research.